The effects of two different recovery protocols on the 100-meter front crawl performance of male swimmers - Štrumbelj, B.; Ušaj, A. (Kinesiology, 2025)
The aim of this study was to ascertain whether passive recovery with additional sodium hydrogen carbonate (NaHCO3-) ingestion affected 100-m swimming speed differently from active recovery during a simulation of a typical competition, which consisted of two trials with a 60-min recovery period. Nine male swimmers (mean age 20.9 ±1.6 years, stature 1.81 ± 8.5 m and body mass 78.1 ± 12.9 kg) completed two maximal 100-m front-crawl swims separated by a 60-min active recovery and two maximal 100-m front crawl swims separated by a 60-min passive recovery with NaHCO3 ingestion on a different test day. The active recovery protocol resulted in lower [LA] than the recovery with NaHCO3 ingestion (p<.05), while pH, pCO2 and [HCO3-] were higher in the recovery with NaHCO3 ingestion protocol (p<.01). Neither protocol had a significant effect on 100-m swim time. In conclusion, a 60-min active swimming recovery at 65% of maximal velocity on the 100-m crawl or a passive recovery with NaHCO3 intake in the same time interval had no significant effect on the second swimming performance, despite the different effects on pH, [HCO3-], pCO2, and [LA]. In both experimental conditions, no differences in swimming time were found between the first and the second swim.